Perkembangan Sosio-Emosional Anak Di Masa Pandemi Covid-19 - Rogamelia, Risna; Amalia, Fiqih; ., Mubasit (Universitas Islam Negeri Raden Intan Lampung, 2022)
Since March 2020 Covid-19 began to enter Indonesia, elderly people, and people with medical conditions such as diabetes, high blood pressure and heart disease, lung disease, or cancer disease, are usually more prone to becoming seriously ill (Kemenkes). , 2020). Since the pandemic status was established, the government has imposed restrictions on community activities, including teaching and learning activities in schools. Learning from home activities makes children unable to carry out their activities at school. The covid-19 pandemic has lasted for 2 years, children who at the beginning of the covid-19 pandemic were at the level of Early Childhood Education, now they are at the elementary school level. This means that so far they have not experienced face-to-face activities at school to the fullest. This prompted researchers to conduct research related to the socio-emotional development of children during the COVID-19 pandemic, to get an overview of the conditions of children's socio-emotional development during the COVID-19 pandemic. This research was conducted with a qualitative method using a descriptive approach. As for the data collection, researchers used structured interviews through instruments that have been provided by researchers to know the socio-emotional development of children. With data sources, namely 3 parents who have children who are sitting in elementary school grade 1 and 2 teachers who teach in grade 1 elementary school.